Nano-optoelectronic sensors and devices nanophotonics from design to manufacturing - Xi, Ning; Lai, King Wai Chiu (Elsevier/William Andrew, 2011)
Nanophotonics has emerged as a major technology and applications domain, exploiting the interaction of light-emitting and light-sensing nanostructured materials. These devices are lightweight, highly efficient, low on power consumption, and are cost effective to produce. The authors of this book have been involved in pioneering work in manufacturing photonic devices from carbon nanotube (CNT) nanowires and provide a series of practical guidelines for their design and manufacture, using processes such as nano-robotic manipulation and assembly methods. They also introduce the design and opera.
Includes bibliographical references and index. - Print version record
Keywords: Optical detectors; Optoelectronic devices; Nanotechnology; Nanophotonics; Détecteurs optiques; Dispositifs optoélectroniques; Nanophotonique; Nanotechnologie; TECHNOLOGY & ENGINEERING; Sensors